Clinical and radiographic outcomes of distal radius fracture treatment with Carbon-Fiber-Reinforced- Polymer Volar Plates (CFRPEEK): analysis of 40 cases - Paracuollo, Mario; Coscione, Andrea Vittorio; Coppola, Alberto; Pellegrino, Giuseppe; Pellegrino, Achille (Lo Scalpello - Journal, 2022)
Introduction. To optimize fracture healing, Carbon- Fiber-Reinforced-Polyetheretherketon Polymer (CFR-PEED) implants have been developed as an alternative to metal plating. Material- specific advantages include X-ray radiolucency, better bone-like elastic modulus, lower bending stiffness and avoidance of the “cold welding” phenomenon. The purpose of this study was to evaluate the clinical and radiographic results after distal radius fracture fixation with Carbon-Fiber-Reinforced-Polymer Volar Plates at 12 months follow- up. Materials and methods. We included 40 patients with AO type 23-B and 23-C radius fractures who were treated with CFR-PEEK volar plate fixation. Clinical and radiographical evaluation were scheduled up to 12 months after surgery. Results. At 12-month follow-up no adverse events were reported. All fractures had healed, and radiographic union was observed at 3 months. The final Quick-DASH average score diminished of 75% and the active ROM almost doubled. Discussion. The X-ray transparency of the device allows easier and truthful intra-operative assessment of the articular surface and facilitates its anatomical reduction, which is harder to achieve with standard metal plates, improving the functional recovery of the wrist. Conclusions. Anatomical design, radiolucency and the presence of polyaxial locking screws orientation make the CFR-PEEK volar plate a suitable device for the treatment of both old and young patients, with simple and complex wrist fracture patterns.